2015
DOI: 10.1055/s-0034-1392550
|View full text |Cite
|
Sign up to set email alerts
|

Colonoscopy with robotic steering and automated lumen centralization: a feasibility study in a colon model

Abstract: Colonoscopy with RS-ALC is technically feasible and appears to be easier and more intuitive than conventional steering for endoscopy-naive novices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 12 publications
0
16
0
Order By: Relevance
“…Colonoscopy with robotic steering and automated lumen centralization (RS-ALC, Enschede, Netherlands) (non-approved) is a colonoscope platform provided with electromechanically controlled wheels that allow automated lumen centralization. A preclinical study showed that this system was able to improve the intubation time and the polyp detection rate among novices but not expert endoscopists [6].…”
Section: Robot-assisted Flexible Eendoscopymentioning
confidence: 99%
“…Colonoscopy with robotic steering and automated lumen centralization (RS-ALC, Enschede, Netherlands) (non-approved) is a colonoscope platform provided with electromechanically controlled wheels that allow automated lumen centralization. A preclinical study showed that this system was able to improve the intubation time and the polyp detection rate among novices but not expert endoscopists [6].…”
Section: Robot-assisted Flexible Eendoscopymentioning
confidence: 99%
“…It was known that novices were more positive than experts about the new platform and mean cecal intubation time of novice with RS-ALC was 781 seconds. 4 The master-slave endoscopic operation robot…”
Section: Colonoscopy With Robotic Steering and Automated Lumen Centramentioning
confidence: 99%
“…The tip of the endoscope may be driven remotely by the operator or through the image-based navigation algorithm. The operability of the system has been evaluated in a validated colon model, which showed that the system enabled novices, but not experienced endoscopists, to reach the cecum faster during colonoscopy [30]. Moreover, the novices detected more polyps when this system was used.…”
Section: Technology Solutions For Advanced Endoscopymentioning
confidence: 99%